2017
DOI: 10.1111/bjdp.12229
|View full text |Cite
|
Sign up to set email alerts
|

Strong and strategic conformity understanding by 3‐ and 5‐year‐old children

Abstract: 'Strong conformity' corresponds to the public endorsement of majority opinions that are in blatant contradiction to one's own correct perceptual judgements of the situation. We tested strong conformity inference by 3- and 5-year-old children using a third-person perspective paradigm. Results show that at neither age, children spontaneously expect that an ostracized third-party individual who wants to affiliate with the majority group will show strong conformity. However, when questioned as to what the ostraciz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…Typical development is indeed replete with relevant, more generalizable, and primordial facts compared with those used by Whitehouse in his extreme account. Developmental research tends to show that the first signs of identity fusion and the explicit sense of oneness with the group begins to become evident during preschool years (3-5 years), with the emergence of gender and racial biases and minimal group affiliation, including the early detection of and preference for higher economic status, as well as first evidence of strong and strategic conformity, from both a first-person and a third-person perspective (Cordonier et al 2017;Haun & Tomasello 2011;Nesdale 2008;Nesdale et al 2005;Shutts 2015;Shutts et al 2016). Resonating with Whitehouse's model of extreme self-sacrifice, children's early signs of identity fusion are compounded by an early propensity toward essentialism (Gelman 2003).…”
Section: Origins Of Social Fusion Philippe Rochatmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical development is indeed replete with relevant, more generalizable, and primordial facts compared with those used by Whitehouse in his extreme account. Developmental research tends to show that the first signs of identity fusion and the explicit sense of oneness with the group begins to become evident during preschool years (3-5 years), with the emergence of gender and racial biases and minimal group affiliation, including the early detection of and preference for higher economic status, as well as first evidence of strong and strategic conformity, from both a first-person and a third-person perspective (Cordonier et al 2017;Haun & Tomasello 2011;Nesdale 2008;Nesdale et al 2005;Shutts 2015;Shutts et al 2016). Resonating with Whitehouse's model of extreme self-sacrifice, children's early signs of identity fusion are compounded by an early propensity toward essentialism (Gelman 2003).…”
Section: Origins Of Social Fusion Philippe Rochatmentioning
confidence: 99%
“…In children, peer pressure begins in the preschool years, with the emergence of strong and strategic conformity (Cordonier et al 2017). If strong and strategic conformity consists of the sophisticated expressions of the need to fuse with the group (BAN), infancy research shows that its source is located way upstream, namely, in the innate propensity to imitate and newborns' inclination to be emotionally contaminated by others (Rochat 2001).…”
Section: Origins Of Social Fusion Philippe Rochatmentioning
confidence: 99%
“…Interestingly, research concerning other social learning forms reported similar age differences, which indirectly confirmed our finding. For example, in a strong conformity task, 5-year-olds, not younger children, construed conformity as a strategy to win group acceptance [40]. Moreover, considering the research on overimitation, older children imitated more unnecessary behaviors than young children [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Typical development is indeed replete with relevant, more generalizable, and primordial facts compared with those used by Whitehouse in his extreme account. Developmental research tends to show that the first signs of identity fusion and the explicit sense of oneness with the group begins to become evident during preschool years (3–5 years), with the emergence of gender and racial biases and minimal group affiliation, including the early detection of and preference for higher economic status, as well as first evidence of strong and strategic conformity, from both a first-person and a third-person perspective (Cordonier et al 2017; Haun & Tomasello 2011; Nesdale 2008; Nesdale et al 2005; Shutts 2015; Shutts et al 2016). Resonating with Whitehouse's model of extreme self-sacrifice, children's early signs of identity fusion are compounded by an early propensity toward essentialism (Gelman 2003).…”
mentioning
confidence: 99%
“…In children, peer pressure begins in the preschool years, with the emergence of strong and strategic conformity (Cordonier et al 2017). If strong and strategic conformity consists of the sophisticated expressions of the need to fuse with the group (BAN), infancy research shows that its source is located way upstream, namely, in the innate propensity to imitate and newborns’ inclination to be emotionally contaminated by others (Rochat 2001).…”
mentioning
confidence: 99%